A Mechanism for Highly Efficient Electrochemical Bubbling Delamination of CVD‐Grown Graphene from Metal Substrates. Issue 8 (30th November 2015) - Liu, Lihui; Liu, Xin; Zhan, Zhaoyao; Guo, Weiling; Xu, Chen; Deng, Jun; Chakarov, Dinko; Hyldgaard, Per; Schröder, Elsebeth; Yurgens, August; Sun, Jie
Abstract : In most cases, transfer of chemical‐vapor‐deposited 2D materials from metallic foil catalysts onto a target substrate is the most necessary step for their promising fundamental studies and applications. Recently, a highly efficient and nondestructive electrochemical delamination method has been proposed as an alternative to the conventional etching transfer method, which alleviates the problem of cost and environment pollution because it eliminates the need to etch away the metals. Here, the mechanism of the electrochemical bubbling delamination process is elucidated by studying the effect of the various electrolytes on the delamination rate. A capacitor‐based circuit model is proposed and confirmed by the electrochemical impedance spectroscopy results. A factor of 27 decrease in the time required for complete graphene delamination from the platinum cathodes is found when increasing the NaOH ratio in the electrolyte solution. The opposite trend is observed for delamination at the anode. The surface screening effect induced by nonreactive ions in the vicinity of the electrodes plays a key role in the delamination efficiency. The analysis is generic and can be used as a guideline to describe and design the electrochemical delamination of other 2D materials from their metal catalysts as well. Abstract : A mechanism for efficient/nondestructive graphene electrochemical transfer using gas bubbles is revealed, alleviating the cost and pollution problems of traditional metal etching. A capacitor‐based circuit model is proposed. The delamination time from metal cathodes decreases 27× as increasing the NaOH ratio in the electrolyte. The screening effect from the nonreactive ions in the electrode vicinity plays a key role.